Latex foam

By incorporating magnetic metal powder with a median diameter of less than 50 μm in latex foam, the challenges of dispersing large amounts of magnetic powder are overcome, resulting in a soft and uniform foam with enhanced magnetostrictive properties and improved manufacturing efficiency.

JP2024178783APending Publication Date: 2024-12-25INOAC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023097195
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2024-12-25

AI Technical Summary

Technical Problem

Existing foamed materials face challenges in maintaining softness and workability due to the difficulty in dispersing large amounts of magnetic powder, which affects the foaming ratio and the ability to change shape and hardness in response to magnetic fields.

Method used

The use of magnetic metal powder with a median diameter of less than 50 μm in latex foam, combined with specific ratios of resin and additives, improves workability and maintains a fine, uniform cell structure.

Benefits of technology

The solution results in a latex foam with improved softness and uniformity, enabling effective magnetostrictive and inverse magnetostrictive effects, while enhancing manufacturing efficiency and preventing foaming defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178783000001_ABST
    Figure 2024178783000001_ABST
Patent Text Reader

Abstract

To provide a technique that achieves improved operability in a manufacturing process of magnetic foams while improving quality of the manufactured foams having magnetism.SOLUTION: The present technique provides a latex foam containing a resin and magnetic metal powder with a median size of less than 50 μm. The latex foam according to the present technique may contain 200 pts.mass or less of the magnetic metal powder relative to 100 pts.mass of the resin. The latex foam according to the present technique may have Asker C hardness of 50 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present technology relates to latex foams. [Background technology]

[0002] A magnetic elastomer, in which magnetic metal powder is dispersed in a soft material, can change shape and hardness in response to the influence of the surrounding magnetic field, exhibiting so-called magnetostriction. Various technologies utilizing the magnetostriction effect of magnetic elastomers are being developed. For example, Patent Document 1 discloses a technology for producing a highly elastic magnetic field responsive soft material, the elastic modulus of which changes significantly when a magnetic field is applied, by using a polyurethane elastomer composition in which magnetic particles are dispersed in a polyether compound having an aromatic ring and a polyisocyanate compound having an aromatic ring.

[0003] On the other hand, technology has also been developed that utilizes the inverse magnetostrictive effect, which is the opposite effect of magnetostrictiveness, in which the response of a magnetic body to a magnetic field changes when a magnetic body is distorted. For example, Patent Document 2 discloses a technology in which a foamed elastomer with magnetic powder dispersed therein is placed inside a coil, and the foamed elastomer containing the magnetic powder is elastically deformed to generate electricity.

[0004] Technologies related to foams having magnetic materials have also been developed. For example, Patent Document 3 discloses a technology for producing a polyurethane foam molded product having high thermal conductivity and electrical insulation, which comprises a base material made of polyurethane foam and composite particles blended in the base material and aligned in a connected relationship, the composite particles comprising thermally conductive particles made of a non-magnetic material, and a coating layer having an insulating film made of a metal oxide and a magnetic material that coats the surfaces of the thermally conductive particles. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2019-210311 A [Patent Document 2] Patent Publication No. 2021-72677 [Patent Document 3] JP 2014-65159 A Summary of the Invention [Problem to be solved by the invention]

[0006] In magnetic elastic bodies aiming at the magnetostrictive effect, materials that can dynamically change shape and hardness when a magnetic field is applied are required. In order to increase the range of change due to the magnetostrictive effect, it is necessary to mix a large amount of magnetic powder, but mixing a large amount of magnetic powder makes the material harder, making it difficult to change shape and hardness. Therefore, it is thought that foamed materials have more internal space than non-foamed materials, and are therefore more likely to maintain their softness.

[0007] On the other hand, for magnetic elastic bodies aiming at the inverse magnetostrictive effect, materials that generate a large amount of electricity when deformed are required. It is known that in order to increase the amount of electricity generated, it is better to have a smaller lateral change when the material is compressed. Therefore, it is thought that foams, which have internal spaces and a smaller Poisson's ratio than non-foamed elastomer materials, are more advantageous for the inverse magnetostrictive effect.

[0008] Against this background, the development of foams using magnetic powder has been progressing, but there have been problems such as difficulty in increasing the amount of magnetic powder due to problems with the magnetic powder being difficult to disperse and settling during foam production, and a decrease in the foaming ratio when a large amount of magnetic powder is added.

[0009] Therefore, a main object of the present technology is to provide a technology that can realize improvement in workability during production of a magnetic foam and improvement in the quality of the produced foam. [Means for solving the problem]

[0010] As a result of intensive research into solving the above problems, the inventors of the present application have succeeded in improving workability during production and the quality of the produced foam by using magnetic metal powder of a specific particle size as the magnetic material and adopting latex foam as the foam, thereby completing the present technology.

[0011] That is, in the present technology, first, a resin and A magnetic metal powder having a median diameter of less than 50 μm; A latex foam is provided which contains The latex foam according to the present technology may contain 200 parts by mass or less of the magnetic metal powder per 100 parts by mass of the resin. The latex foam according to the present technology can have an Asker C hardness of 50 or less. [Brief description of the drawings]

[0012] [Figure 1] 1 shows micrographs of the latex foams of Comparative Example 1, Example 4, Example 6, and Example 8 taken with an optical microscope at a magnification of 100 times. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] A preferred embodiment for carrying out the present technology will be described below. The embodiments described below are representative examples of the present technology, and any of the embodiments can be combined. In addition, the scope of the present technology is not narrowly interpreted by these.

[0014] 1. Composition for producing latex foam The latex foam according to the present technology is produced using a composition for producing latex foam. The composition for producing latex foam contains a resin latex and a magnetic metal powder. The composition for producing latex foam may contain a crosslinking agent, a crosslinking accelerator, a crosslinking assistant, a plasticizer, a surfactant, a gelling agent, and various other components that can be used in the production of latex foam depending on the purpose. Each component will be described in detail below.

[0015] (1) Resin latex The resin latex that can be used in this technology is a non-crosslinked or partially crosslinked polymer of resin (hereinafter referred to as "resin polymer") dispersed in water as particles. For example, when the resin polymer is natural rubber, rubber sap, a concentrated version of rubber sap, or rubber sap or the like further blended with a preservative or the like can be used. When the resin polymer is synthetic rubber, rubber latex prepared by emulsion polymerization or rubber latex prepared by emulsifying a polymer obtained by a method such as solution polymerization with a surfactant and water and removing the solvent as necessary can be used.

[0016] The resin polymer that can be used in the present technology is a resin polymer in the broad sense, and the resin polymer in the broad sense includes rubber polymers and elastomers in addition to the resin polymer in the narrow sense. As the rubber polymer, for example, a polymer containing one or more of ethylene, propylene, styrene, butadiene, isoprene, chloroprene, acrylic acid esters, methacrylic acid esters, acrylonitrile, vinyl acetate, acrylamide, acrylamide derivatives, vinyl ethers, vinylpyrrolidone, etc. as a monomer unit can be used. More specifically, examples of the rubber include nitrile rubber (NBR), styrene-butadiene rubber (SBR), silicone rubber, urethane rubber (U), ethylene-propylene rubber (EPM, EPDM), chloroprene rubber (CR), natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), 1,2-polybutadiene rubber (1,2-BR), butyl rubber (IIR), chlorosulfonated polyethylene rubber (CSM), acrylic rubber (ACM, ANM), acrylate-butadiene rubber, methyl methacrylate-butadiene rubber (MBR), epichlorohydrin rubber (CO, ECO), polysulfide rubber (T), fluororubber (FKM), etc. In addition to the latexes of these rubbers, styrene-butadiene-vinylpyridine-based latex, DPL (depolymerized latex), rubber polymers in chlorosulfonated polyethylene latex, etc. can also be used. Examples of the elastomer include olefin-based elastomer (TPO), styrene-based elastomer (TPS), polyurethane-based elastomer (TPU), polyester-based elastomer (TPEE), polyvinyl chloride-based elastomer (TPVC), etc. Examples of the resin in the narrow sense include silicone-based resin, acrylic-based resin, polyolefin-based resin, polyurethane-based resin, etc., and a specific example is polyvinyl chloride (PVC).

[0017] (2)Magnetic metal powder This technology uses magnetic metal powder with a median diameter of less than 50 μm. Using magnetic metal powder with a median diameter of less than 50 μm improves workability during the production of latex foam and has little effect on the foaming and crosslinking reactions, suppressing the decrease in expansion ratio and enabling the production of latex foam with fine and uniform cell structure.

[0018] The upper limit of the median diameter of the magnetic metal powder used in the present technology is preferably 30 μm or less, more preferably 25 μm or less, and even more preferably 20 μm or less, while the action and effect of the present technology can be exhibited if the upper limit is less than 50 μm. The lower limit of the median diameter of the magnetic metal powder used in the present technology can be freely set as long as it does not impair the purpose and action and effect of the present technology, and is, for example, 0.5 μm or more, preferably 1 μm or more, more preferably 1.5 μm or more, and even more preferably 2.0 μm or more.

[0019] As the magnetic metal used as the magnetic metal powder, one or more general magnetic metals can be freely combined and used as long as the purpose and effect of the present technology are not impaired. In the present technology, it is possible to freely combine hard magnetic metals and soft magnetic metals as the magnetic metals. A hard magnetic metal is a metal that, after being magnetized by an external magnetic field, retains its magnetic force even when the external magnetic field is removed, and a soft magnetic metal is a metal that loses its magnetic force when the external magnetic field is removed. In the present technology, hard magnetic metal powder and soft magnetic metal powder can be used separately depending on the purpose.

[0020] Specific examples of magnetic metals that can be used in the present technology include neodymium magnets (NdFe 14 B), neodymium (Nd), iron, silicon iron, carbonyl iron, Fe-Ni alloy (permalloy), Fe-Si-Al alloy (sendust), Fe-Co alloy (permendur), electromagnetic stainless steel, Fe-Si alloy, Fe-Al alloy, Fe-Si-Cr alloy, Fe-Ni-Co alloy (mu-metal), Fe-Ni-Mo alloy (supermalloy), Fe-Co alloy, Fe-Si-Al-Cr alloy, Fe-Si-B alloy, Fe-Si-Co-B alloy, etc.

[0021] The amount of magnetic metal powder used in the composition for producing latex foam of the present technology can be freely set as long as it does not impair the purpose and effect of the present technology. In the present technology, the lower limit of the content of magnetic metal powder in the composition for producing latex foam is, for example, 10 parts by mass or more, preferably 15 parts by mass or more, more preferably 20 parts by mass or more, relative to 100 parts by mass of resin latex. By setting the amount of magnetic metal powder used within this range, in a magnetic foam aiming at a magnetostrictive effect, the change width due to the magnetostrictive effect can be made larger, and in a magnetic foam aiming at an inverse magnetostrictive effect, the amount of power generated when deformed can be made larger.

[0022] In the present technology, the upper limit of the amount of magnetic metal powder used is, for example, 250 parts by mass or less, preferably 200 parts by mass or less, more preferably 150 parts by mass or less, and even more preferably 100 parts by mass or less, relative to 100 parts by mass of the resin latex. By setting the amount of magnetic metal powder used within this range, it is possible to further improve the workability during production, prevent poor foaming, and improve moldability.

[0023] (3) Crosslinking agent A crosslinking agent can be used in the composition for producing latex foam of the present technology. As the crosslinking agent that can be used in the present technology, one or more crosslinking agents that can be used in the production of latex foam can be freely selected and used as long as they do not impair the purpose and effect of the present technology.

[0024] Examples of crosslinking agents include sulfur, organic peroxides, and phenolic compounds. In the case of crosslinking with sulfur, colloidal sulfur and fine powdered sulfur, as well as sulfur compounds such as sulfur dichloride and dipentamethylene thiuram tetrasulfide, can be used. In the case of crosslinking with organic peroxides, organic peroxides such as hydroperoxides, acyl peroxides, alkyl peroxides, peroxy esters, peroxy ketals, and peroxy carbonates can be used. The organic peroxides may be blended as they are, or may be stabilized by adsorbing them to inorganic powders, dissolving them in hydrocarbons or plasticizers, or mixing them with inert liquids such as polydimethylsiloxane. In the case of crosslinking with phenolic compounds, alkylphenol-formaldehyde resins, sulfurized p-tert-butylphenol resins, and alkylphenol-sulfide resins can be used.

[0025] The amount of the crosslinking agent used in the composition for producing latex foam of the present technology can be freely set as long as it does not impair the purpose and effect of the present technology. In the present technology, the lower limit of the content of the crosslinking agent in the composition for producing latex foam is, for example, 0.2 parts by mass or more, preferably 0.4 parts by mass or more, more preferably 0.6 parts by mass or more, per 100 parts by mass of the resin latex. By setting the amount of the crosslinking agent used within this range, the viscosity of the mixture before foaming and crosslinking can be increased, thereby improving the foamability. In addition, the mechanical properties of the latex foam can be improved.

[0026] In the present technology, the upper limit of the amount of the crosslinking agent used is, for example, 5.0 parts by mass or less, preferably 4.0 parts by mass or less, and more preferably 3.0 parts by mass or less, relative to 100 parts by mass of the resin latex. By setting the amount of the crosslinking agent used within this range, it is possible to prevent poor foaming and improve moldability.

[0027] (4) Crosslinking accelerator A crosslinking accelerator can be used in the composition for producing latex foam of the present technology. As the crosslinking accelerator that can be used in the present technology, one or more crosslinking accelerators that can be used in the production of latex foam can be freely selected and used as long as they do not impair the purpose and effect of the present technology.

[0028] Examples of the crosslinking accelerator include thiazoles such as 2-mercaptobenzothiazole and its salts (sodium salt, zinc salt, cyclohexylamine salt, dicyclohexylamine salt, etc.), 2-(4'-morpholinodithio)benzothiazole, 4-morpholinyl-2-benzothiazyl disulfide, and 2-(N,N-diethylthiocarbamoylthio)benzothiazole; zinc dithiocarbamates such as zinc dimethyldithiocarbamate, zinc diethyldithiocarbamate, zinc di-n-butyldithiocarbamate, zinc dibenzyldithiocarbamate, zinc ethylphenyldithiocarbamate, and zinc N-pentamethylenedithiocarbamate; tetramethylthiuramoyl Examples of the thiuram tetrasulfide include thiurams such as N,N-dimethyl-N,N-diphenylthiuram disulfide, tetramethylthiuram disulfide, tetraethylthiuram disulfide, tetrabutylthiuram disulfide, N,N'-dimethyl-N,N'-diphenylthiuram disulfide, and dipentamethylenethiuram tetrasulfide; sulfenamides such as N,N-diisopropyl-2-benzothialylsulfenamide, Nt-butyl-2-benzothialylsulfenamide, N-cyclohexyl-2-benzothiazylsulfenamide, N,N-dicyclohexyl-2-benzothiazylsulfenamide, and N-oxydiethylene-2-benzothiazylsulfenamide; and mixtures thereof.

[0029] The amount of the crosslinking accelerator used in the composition for producing latex foam of the present technology can be freely set as long as it does not impair the purpose and effect of the present technology. In the present technology, the lower limit of the content of the crosslinking accelerator in the composition for producing latex foam is, for example, 0.1 parts by mass or more, preferably 0.2 parts by mass or more, more preferably 0.5 parts by mass or more, relative to 100 parts by mass of the resin latex. By setting the amount of the crosslinking accelerator used within this range, the crosslinking speed can be increased, gas leakage can be suppressed, and the foamability during production can be improved. In addition, the mechanical properties of the latex foam can be improved.

[0030] In the present technology, the upper limit of the amount of the crosslinking accelerator used is, for example, 10 parts by mass or less, preferably 5 parts by mass or less, and more preferably 3 parts by mass or less, relative to 100 parts by mass of the resin latex. By setting the amount of the crosslinking accelerator used within this range, it is possible to prevent non-foaming due to an excessive increase in the crosslinking speed, and to improve the moldability of the latex foam.

[0031] (5) Crosslinking assistant A crosslinking aid can be used in the composition for producing latex foam of the present technology. As the crosslinking aid that can be used in the present technology, one or more crosslinking aids that can be used in the production of latex foam can be freely selected and used as long as they do not impair the purpose and effect of the present technology.

[0032] Examples of the crosslinking assistant include metal oxides such as zinc oxide (zinc oxide), magnesium oxide, etc. Among these, in the present technology, it is preferable to use zinc oxide from the viewpoint of adjusting the timing of the foaming rate and the crosslinking rate.

[0033] The amount of the crosslinking aid used in the composition for producing latex foam of the present technology can be freely set as long as it does not impair the purpose and effect of the present technology. In the present technology, the lower limit of the content of the crosslinking aid in the composition for producing latex foam is, for example, 0.1 parts by mass or more, preferably 0.2 parts by mass or more, more preferably 1 part by mass or more, relative to 100 parts by mass of the resin latex. By setting the amount of the crosslinking aid used within this range, the crosslinking speed can be increased, gas leakage can be suppressed, and the foamability during production can be improved. In addition, the mechanical properties of the latex foam can be improved.

[0034] In the present technology, the upper limit of the amount of the crosslinking aid used is, for example, 10 parts by mass or less, preferably 7 parts by mass or less, and more preferably 4 parts by mass or less, relative to 100 parts by mass of the resin latex. By setting the amount of the crosslinking aid used within this range, it is possible to prevent non-foaming due to an excessive increase in the crosslinking speed, and to improve the moldability of the latex foam.

[0035] (6) Plasticizers A plasticizer can be used in the composition for producing latex foam of the present technology. As the plasticizer that can be used in the present technology, one or more plasticizers that can be used in the production of latex foam can be freely selected and used as long as they do not impair the purpose and effect of the present technology.

[0036] Examples of plasticizers include vegetable oils and animal oils such as olive oil, castor oil, safflower oil, cottonseed oil, linseed oil, rapeseed oil, soybean oil, peanut oil, palm oil, coconut oil, and corn oil, as well as fatty acid ester oils of biological origin obtained by dehydrating or hydrogenating them, such as dehydrated castor oil; hydrocarbon process oils such as paraffinic process oil, naphthenic process oil, and aromatic process oil; hydrocarbon oils such as spindle oil, petrolatum, and liquid paraffin; and dibutyl phthalate. , dioctyl phthalate, di-(2-ethylhexyl) phthalate, di(2-ethylhexyl) tetrahydrophthalate, di-n-octyl adipate, di(2-ethylhexyl) adipate, diisodecyl adipate, tricresyl phosphate, alkyl allyl phosphate, butylphthalyl butyl glycolate, di-n-butyl sebacate, di(2-ethylhexyl) sebacate, triethylene glycol di(2-ethyl hexoate), acetyl tri-n-butyl citrate, etc.

[0037] The amount of plasticizer used in the composition for producing latex foam of the present technology can be freely set as long as it does not impair the purpose and effect of the present technology. In the present technology, the lower limit of the content of the plasticizer in the composition for producing latex foam is, for example, 0.1 parts by mass or more, preferably 1 part by mass or more, and more preferably 2 parts by mass or more, per 100 parts by mass of the resin latex. By setting the amount of the plasticizer used within this range, the mechanical properties of the latex foam can be improved.

[0038] In the present technology, the upper limit of the amount of the plasticizer used is, for example, 8 parts by mass or less, preferably 7 parts by mass or less, and more preferably 5 parts by mass or less, based on 100 parts by mass of the resin latex. By setting the amount of the plasticizer used within this range, the moldability of the latex foam can be improved.

[0039] (7) Surfactants A surfactant can be used in the composition for producing latex foam of the present technology. As the surfactant that can be used in the present technology, one or more surfactants that can be used in the production of latex foam can be freely selected and used as long as the purpose and effect of the present technology are not impaired.

[0040] (7-1) Nonionic surfactants The composition for producing latex foam of the present technology can use a nonionic surfactant as the surfactant. A nonionic surfactant is a surfactant having a hydrophilic group and a hydrophobic group, and has a hydrophilic group that does not ionize when dissolved in water (does not undergo ionic dissociation in water).

[0041] As the nonionic surfactant that can be used in the present technology, one or more nonionic surfactants that can be used in the production of latex foam can be freely selected and used as long as the purpose and effect of the present technology are not impaired. Examples of the nonionic surfactant include polyalkylene glycol type nonionic surfactants having an ether bond as a hydrophilic group, polyhydric alcohol type nonionic surfactants having a hydroxyl group as a hydrophilic group, etc. Examples of the hydrophobic group include an aliphatic hydrocarbon group, an aromatic hydrocarbon group, and an aromatic hydrocarbon group having an aliphatic side chain.

[0042] In the present technology, it is preferable to use a derivative of polyalkylene glycol (polyalkylene glycol type nonionic surfactant) as a nonionic surfactant. Examples of the derivative of polyalkylene glycol include polyoxyalkylene alkyl ethers such as polyoxyalkylene monoalkyl ethers and polyoxyalkylene dialkyl ethers, polyoxyalkylene alkenyl ethers such as polyoxyalkylene monoalkenyl ethers and polyoxyalkylene dialkenyl ethers, polyoxyalkylene aryl ethers such as polyoxyalkylene monoaryl ethers and polyoxyalkylene diaryl ethers, polyoxyalkylene alkylphenyl ethers, polyoxyalkylene glycol fatty acid esters such as polyoxyalkylene glycol mono fatty acid esters and polyoxyalkylene glycol di fatty acid esters, polyoxyalkylene sorbitan fatty acid esters, polyoxyalkylene alkylamines, polyoxyalkylene diamines, etc.

[0043] The amount of the nonionic surfactant used in the composition for producing latex foam of the present technology can be freely set as long as it does not impair the purpose and effect of the present technology. In the present technology, the lower limit of the content of the nonionic surfactant in the composition for producing latex foam is, for example, 0.1 parts by mass or more, preferably 1 part by mass or more, more preferably 2 parts by mass or more, relative to 100 parts by mass of the resin latex. By setting the amount of the nonionic surfactant used within this range, it is possible to improve the foamability during production, improve the moldability of the latex foam, and produce a latex foam having fine cells.

[0044] In the present technology, the upper limit of the amount of the nonionic surfactant used is, for example, 20 parts by mass or less, preferably 15 parts by mass or less, and more preferably 12 parts by mass or less, relative to 100 parts by mass of the resin latex. By setting the amount of the nonionic surfactant used within this range, the mechanical properties of the latex foam can be improved.

[0045] (7-2) Surfactants other than nonionic surfactants In the composition for producing latex foam of the present technology, surfactants other than nonionic surfactants can also be used as the surfactant. Examples of surfactants other than nonionic surfactants include anionic surfactants in which the hydrophobic group portion is ionized to negative ions when dissolved in water, cationic surfactants in which the hydrophobic group portion is ionized to positive ions when dissolved in water, and amphoteric surfactants that exhibit the properties of anionic surfactants in the alkaline region and the properties of cationic surfactants in the acidic region when dissolved in water.

[0046] Examples of anionic surfactants include milk proteins such as casein, and alkali metal salts of alkylbenzenesulfonic acid. Examples of cationic surfactants include stearyldimethylammonium chloride, benzalkonium chloride, etc. Examples of amphoteric surfactants include amino acid type, betaine type, amine oxide type, and other amphoteric surfactants.

[0047] The amount of the surfactant other than the nonionic surfactant used in the composition for producing latex foam of the present technology can be freely set as long as it does not impair the purpose and effect of the present technology. In the present technology, the lower limit of the content of the surfactant other than the nonionic surfactant in the composition for producing latex foam is, for example, 0.05 parts by mass or more, preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, relative to 100 parts by mass of the resin latex. By setting the amount of the surfactant other than the nonionic surfactant used within this range, the bubble film during production can be stabilized.

[0048] In the present technology, the upper limit of the amount of the surfactant other than the nonionic surfactant used is, for example, 5 parts by mass or less, preferably 3 parts by mass or less, more preferably 2 parts by mass or less, relative to 100 parts by mass of the resin latex. By setting the amount of the surfactant other than the nonionic surfactant used within this range, gelation problems due to excessive stabilization of the bubble film during production can be prevented.

[0049] (8) Gelling agent A gelling agent can be used in the composition for producing latex foam of the present technology. By using a gelling agent, the chemical stability of the polymer particles present in the emulsion composition in the state of an emulsion, i.e., in the state of an emulsion, can be reduced, and the particles can be aggregated to form a so-called gelled state. As the gelling agent that can be used in the present technology, one or more gelling agents that can be used in the production of latex foam can be freely selected and used, as long as the purpose and effect of the present technology are not impaired.

[0050] Examples of the gelling agent include hexafluorosilicates such as sodium silicofluoride, potassium silicofluoride, and calcium silicofluoride; and cyclohexylamine salts such as acetate and sulfamate of cyclohexylamine.

[0051] The amount of gelling agent used in the composition for producing latex foam of the present technology can be freely set as long as it does not impair the purpose and effect of the present technology. In the present technology, the lower limit of the content of the gelling agent in the composition for producing latex foam is, for example, 0.5 parts by mass or more, preferably 1 part by mass or more, more preferably 2 parts by mass or more, relative to 100 parts by mass of the resin latex. By setting the amount of the gelling agent used within this range, the foamability during production can be improved, and the moldability of the latex foam can be improved.

[0052] In the present technology, the upper limit of the amount of the gelling agent used is, for example, 15 parts by mass or less, preferably 12 parts by mass or less, and more preferably 10 parts by mass or less, relative to 100 parts by mass of the resin latex. By setting the amount of the gelling agent used within this range, the mechanical properties of the latex foam can be improved.

[0053] (9)Other In the composition for producing latex foam of the present technology, one or more components that can be freely selected from various components that can be used in the production of latex foam depending on the purpose can be used as other components, as long as the purpose and effects of the present technology are not impaired.

[0054] Examples of components that can be used in the composition for producing latex foam according to the present technology include antioxidants, stabilizers, colorants, dispersants, UV absorbers, antibacterial agents, antifungal agents, thickeners, etc.

[0055] 2.Latex foam The latex foam according to the present technology is produced using the above-mentioned composition for producing a latex foam.

[0056] As shown in the photographs of the examples described later, the latex foam according to the present technology has a fine and uniform cell structure despite the presence of magnetic metal. In addition, the latex foam according to the present technology is characterized by having good softness.

[0057] The apparent specific gravity of the latex foam of this technology (actual weight (g) / volume measurement (cm 3 )) is not particularly limited as long as it does not impair the purpose and effect of the present technology. The lower limit of the apparent specific gravity of the latex foam according to the present technology is, for example, 0.4 g / cm 3 More than 0.5g / cm 3 More than 0.6g / cm 3 The upper limit of the apparent specific gravity of the latex foam according to the present technology is, for example, 1.0 g / cm 3 Less than 0.9 g / cm 3 Less than or equal to 0.8 g / cm 3 The following is the result.

[0058] The Asker C hardness of the latex foam according to the present technology is not particularly limited as long as it does not impair the purpose and effect of the present technology. The lower limit of the Asker C hardness of the latex foam according to the present technology is, for example, 5 or more, 10 or more, or 15 or more. The upper limit of the Asker C hardness of the latex foam according to the present technology is, for example, 60 or less, preferably 50 or less, more preferably 40 or less, and even more preferably 30 or less. In the present technology, the Asker C hardness is a value measured according to the method specified in the Society of Rubber Industry, Japan Standard (SRIS 0101).

[0059] 3.Applications of latex foam The latex foam according to the present technology can be used in various applications by utilizing its magnetic properties and fine and uniform cell structure. For example, it can be suitably used in applications utilizing the magnetostrictive effect or the inverse magnetostrictive effect. More specifically, it can be used for applications such as vibration control, heat conduction control by magnetic field orientation, mechanical anisotropy by magnetic field orientation, transfer rolls for magnetic toners, magnetic field responsive actuators, power generation, and sensing.

[0060] 4.Latex foam manufacturing method The latex foam according to the present technology can be produced by mixing the components of the composition for producing latex foam according to the present technology described above to prepare a composition, foaming, gelling, and thermal crosslinking. Known methods for producing latex foam include the Dunlop method, in which the composition for producing latex foam is physically (mechanically) foamed and solidified (gelled) at room temperature, and the Talalay method, in which foaming is chemically performed and gelling is performed by freezing. Either method can be used in the present technology, but it is particularly preferable to adopt the Dunlop method.

[0061] The Dunlop process involves a composition preparation step, a foaming / gelling step, a crosslinking step, and other steps. Each step will be described below.

[0062] (1) Composition preparation process The composition preparation step is a step of preparing a composition for producing latex foam. Specifically, in the composition preparation step, various additives such as magnetic metal powder, a crosslinking agent, a crosslinking accelerator, a crosslinking assistant, a plasticizer, and a surfactant are added to a resin latex, and the mixture is thoroughly stirred and mixed with a mixer or the like to prepare a composition for producing latex foam.

[0063] (2) Foaming and gelling process The foaming and gelling process is a process in which a gelling agent and gas are mixed into the prepared composition for manufacturing latex foam, and the mixture is thoroughly stirred and mixed to foam and gel, thereby obtaining a gel-like material.

[0064] In the foaming and gelling process of the present invention, one or more gases that can be used in the production of latex foam can be freely selected and used, as long as the purpose and effect of the present invention are not impaired. For example, air, nitrogen, carbon dioxide, and fluorocarbons that are normally gases at ambient temperature can be used.

[0065] (3) Crosslinking process The crosslinking step is a step in which the gel-like material obtained in the foaming / gelling step is processed into a desired shape by a method such as casting, casting, or extrusion molding, and then heated to promote the crosslinking reaction. The heating temperature in the crosslinking step can be freely set depending on the type of crosslinking agent used, etc.

[0066] After the crosslinking step, desired steps such as demolding, washing, drying, cutting, polishing, etc. may be added depending on the application of the latex foam, to produce a latex foam of a predetermined shape. EXAMPLES

[0067] The present technology will be described in more detail below based on examples. Note that the examples described below are representative examples of the present technology, and the scope of the present technology is not to be interpreted narrowly by these examples.

[0068] <Experimental Example 1> (1) Raw materials Rubber latex: NBR latex Plasticizer: Olive oil Nonionic surfactant and foam enhancer: Polyalkylene glycol derivative (molecular weight: 3069-4560, having C3H6O units) Crosslinker: Sulfur Crosslinking agent: zinc oxide Crosslinking accelerator: Thiazole crosslinking accelerator Antioxidant 1: Phenolic antioxidant UV absorbers / antioxidants 2: Bisphenol-based UV absorbers / antioxidants Anionic surfactant 1: Milk proteins Anionic surfactants 2: Naphthalenesulfonic acid formalin condensate sodium Magnetic metal powder 1: Neodymium magnet powder ("MQFP-089" manufactured by Magnequench) Magnetic metal powder 2: Neodymium magnet powder ("MQP-085" manufactured by Magnequench) Magnetic metal powder 3: Carbonyl iron powder (BASF "CIP CD") Gelling agent: Sodium silicofluoride Suspension agent: Bentonite Dispersant: Sulfonic acid dispersant pH adjuster: Potassium hydroxide

[0069] (2) Latex foam manufacturing Each latex foam was produced according to the Dunlop method using the raw materials shown in Table 1 below. Specifically, first, the raw materials shown in Table 1 below, except for the magnetic metal powder and the gelling agent mixture, were mixed by stirring, and then each magnetic metal powder was added and further mixed by stirring to prepare a composition. The prepared composition was further stirred at an increased stirring speed to foam it, and the gelling agent mixture was added, and the stirring speed was reduced and stirred, and the composition was poured into a mold and left at room temperature. The composition was removed from the mold, dried under reduced pressure, and heated in a thermostatic chamber to produce each latex foam.

[0070] (3) Evaluation The weight and volume of the produced latex foam were measured, and the apparent specific gravity was calculated. In addition, the Asker C hardness of the produced latex foam was measured according to the method specified in the Society of Rubber Industry, Japan Standard (SRIS 0101).

[0071] (4) Results The results are shown in the following Table 1. Moreover, micrographs of the latex foams of Comparative Example 1, Example 4, Example 6, and Example 8 taken with an optical microscope at a magnification of 100 times are shown in FIG. [Table 1]

[0072] (5) Discussion As shown in Table 1 and FIG. 1, in Comparative Example 2, in which magnetic metal powder with a median diameter of 50 μm or more was used, a latex foam could not be produced due to inability to mix, whereas in Examples 1 to 8, in which magnetic metal powder with a median diameter of less than 50 μm was used, a latex foam with a fine and uniform cell structure could be produced.

Claims

1. Resin and Magnetic metal powder having a median diameter of less than 50 μm; A latex foam containing

2. 2. The latex foam according to claim 1, comprising 200 parts by mass or less of the magnetic metal powder per 100 parts by mass of the resin.

3. 2. The latex foam according to claim 1, having an Asker C hardness of 50 or less.

Citation Information

Patent Citations

  • Urethane foam molding and method for producing the same

    JP2014065159A

  • Water-based polyurethane resin composition, and high elastic magnetic field responsive soft material comprising said polyurethane elastomer composition

    JP2019210311A

  • Elastic body, bound stopper, electromagnetic induction device, power generation system, detection device, and method for manufacturing elastic body

    JP2021072677A